Water Level Monitoring System using Internet of Things - P.Menaka; B. M. Shrinithi (International Journal of Engineering and Management Research, 2021)
As a Smart innovation with greatness suggestions gives the better outcome when contrast and Existing System. This work about the water level detecting inside the tank and interface it to Node MCU (which holds wi-fi module to send message) to send status of the tank to Blynk application through Arduino ide code. This gives a thought that the things get associated over organization roll out more brilliant improvement for later. In nowadays everything dependent on the advanced cell and its applications. Along these lines, this venture would be helpful in impending ages. The fundamental point of this framework is to screen the water level at rustic zones with the goal that they can identify the wastage of water and measures can be taken to dodge superfluous flooding of water in the zones where observing is tricky.